Don dan dum diew khon diew dae : . Jak yuk rem ton thueng mahawittayalai (por sor song si pad kao thueng song si kao ha) (Fa Diew Khan publishing)
Covertitle: jak yuk rem ton thueng mahawittayalai (por sor song si pad kao thueng song si kao ha) One man stand to discover. Covertitle also: From the beginning to the University period (1946-1952)